A randomized feasibility pilot trial of hearing treatment for reducing cognitive decline: Results from the Aging and Cognitive Health Evaluation in Elders Pilot Study. Issue 3 (21st June 2017) - Deal, Jennifer A.; Albert, Marilyn S.; Arnold, Michelle; Bangdiwala, Shrikant I.; Chisolm, Theresa; Davis, Sonia; Eddins, Ann; Glynn, Nancy W.; Goman, Adele M.; Minotti, Melissa; Mosley, Thomas; Rebok, George W.; et al.
Abstract: Introduction: Hearing loss (HL) is prevalent and independently related to cognitive decline and dementia. There has never been a randomized trial to test if HL treatment could reduce cognitive decline in older adults. Methods: A 40‐person (aged 70–84 years) pilot study in Washington County, MD, was conducted. Participants were randomized 1:1 to a best practices hearing or successful aging intervention and followed for 6 months. clinicaltrials.gov Identifier: NCT02412254 . Results: The Aging and Cognitive Health Evaluation in Elders Pilot (ACHIEVE‐P) Study demonstrated feasibility in recruitment, retention, and implementation of interventions with no treatment‐related adverse events. A clear efficacy signal of the hearing intervention was observed in perceived hearing handicap (mean of 0.11 to −1.29 standard deviation [SD] units; lower scores better) and memory (mean of −0.10 SD to 0.38 SD). Discussion: ACHIEVE‐P sets the stage for the full‐scale ACHIEVE trial (N = 850, recruitment beginning November 2017), the first randomized trial to determine efficacy of a best practices hearing (vs. successful aging) intervention on reducing cognitive decline in older adults with HL.